PROTECTION OF TRANSMISSION TOWERS AGAINST LIGHTNING DISTURBANCES ON THE 150 KV STAR-RAWALO-MAJENANG OVERHEAD TRANSMISSION LINE - Faozi Firansyah, Bekti; Watiningsih, Tri; Wahjudi, Dody (Journal of Electronic and Electrical Power Applications, 2025)
As A Tropical Country, Indonesia Frequently Experiences Extreme Weather, One Of Which Is Lightning, Which Has The Potential To Harm Humans And Electrical Infrastructure, Particularly On High Voltage Overhead Lines (Sutt). Sutt Play A Crucial Role In The Distribution Of Electrical Energy, But Are Vulnerable To Natural Disturbances That Are Difficult To Control. Lightning Strikes Can Damage Equipment And Reduce System Reliability, Necessitating Effective Protection, Such As Grounding Towers, To Channel Lightning Currents To The Ground. The Research Phase Began With A Literature Review, Examining Theories, Standards, And Previous Research Related To Grounding Systems And Lightning Protection On Transmission Lines. Next, Field Data Was Collected, Including Data On Lightning Disturbances On Sutts, The Existing Condition Of Tower Grounding Systems, And The Types Of Protection Installed. Afterward, Grounding Resistance Measurements Were Conducted On Several Towers To Determine The Quality Of The Existing Grounding System. The Results Showed That The Multi-Direct Grounding Method, With An Average Resistance Value Of 2.89 Ω On The 150 Kv Star-Rawalo-Majenang Sutt, Met Standards And Was Proven Effective In Protecting Towers From Lightning Disturbances, Minimizing The Risk Of Damage Due To Back Flashover, And Improving Transmission System Reliability